Contemporary Challenges of Malaysia Halal industry - Abdullah, Rahman Bin (Advances in Social Sciences Research Journal, 2018)
Halal market has been growing for the past couple of decades. The growth has been spurred by the demands of the Muslims society worldwide, the potential market it shows, the government support and initiatives, the private sector resourcefulness and the increase knowledge and awareness of the Muslims society and the Non-Muslims worldwide. However, although Malaysia has taken a lot of initiatives in ensuring halal industry grows substantially, Malaysia’s governing bodies and the private sector needs to be aware of the challenges the Halal market needs to face in terms of fulfilling the consumer acceptance, religious acceptance, health and convenience and economic acceptance. A proper reasoning and understanding of the halal market and conditions will enable Malaysia to take the halal market to a more substantial level without offending or disregarding any factors in the first place.